Multi-step beef ration optimisation: application of linear and weighted goal programming with a penalty function - Zgajnar, Jaka; Erjavec, Emil; Kavcic, Stane (MTT Agrifood Research Finland, 2010)
The aim of this paper is to present the method and tool for optimisation of beef-fattening diets. Changes in policy environment and changes in costs of feed pose challenges for farm efficiency. We construct a spreadsheet from two modules based on mathematical deterministic programming techniques. In order to obtain an estimate of the magnitude of costs that may be incurred, the first module utilizes a linear program for least-cost ration formulation. The resulting value is then targeted as a cost goal in the second module. This is supported by weighted goal programming with a penalty function system. The approach presented here is an example of how a combination of mathematical programming techniques might be applied to prepare a user-friendly tool for optimal ration formulations. We report results that confirm this approach as useful, since one is able to formulate a least-cost ration without risking a decrease in the ration s nutritive value or affecting the balance between nutrients.
Keywords: linear programming; weighted goal programming; penalty function; spreadsheet ration optimisation; beef farming; beef economics